Výběrová edice archivních karet s vojvodovskou tematikou z výzkumu Ivy Heroldové na jižní Moravě v roce 1973 - Jakoubek, Marek (Lidé města, 2012)
This edition presents the transcription of several archive materials on Vojvodovo, representing the research results of Iva Heroldová, carried out in villages with new settlers in Southern Moravia in 1973. Aside from the detailed formal and subjective characteristics of the source and the explanation of the methods used to process it, the presentation of relevant archive material is preceded by a short summary of the research activities of I. Heroldová and the place that Southern Moravian research and its results take in them. Emphasis is placed especially on the issue of (not) utilising this research in I. Heroldová's studies dedicated to Vojvodovo.